If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n + -1 + 2n = -4 Reorder the terms: -1 + n + 2n = -4 Combine like terms: n + 2n = 3n -1 + 3n = -4 Solving -1 + 3n = -4 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 3n = -4 + 1 Combine like terms: -1 + 1 = 0 0 + 3n = -4 + 1 3n = -4 + 1 Combine like terms: -4 + 1 = -3 3n = -3 Divide each side by '3'. n = -1 Simplifying n = -1
| 18x+7=-5FORX | | 1.2/58 | | 1.2/5.8 | | 27x-3=26x+1 | | 6x/2=33 | | 5x-5=5-5x | | 5x+2=-9 | | -20x^2+17x+24=0 | | 15x=16x-8 | | 4(x^2+5)=2(x^2+1) | | 18-1/2=6 | | 3*1/8= | | 18x+9=19x+2 | | 3xsquared=9 | | 4(3x+2y)-7x-5(2y-4)= | | 224/32= | | 3(-4m-6)=-6(m+3) | | 30*93= | | -38-7k=-8(k+4) | | 32/224 | | -2x-1=-9x-x | | 5/9=1/4x | | 25*79= | | 26x=27x-5 | | 2y^3+3y^2=0 | | 5x+10y=-2 | | 157=-192+h | | 11*38= | | -2z/2 | | 4f-9-3f+10= | | -18=-15-3(6t+5) | | 0(5m)=5m |